Community Resilience, Psychological Resilience, and Depressive Symptoms: An Examination of the Mississippi Gulf Coast 10 Years After Hurricane Katrina and 5 Years After the Deepwater Horizon Oil Spill. (30th August 2017) - Lee, Joohee; Blackmon, Bret J.; Cochran, David M.; Kar, Bandana; Rehner, Timothy A.; Gunnell, Mauri Stubbs
Abstract: Objective: This study examined the role of community resilience and psychological resilience on depressive symptoms in areas on the Mississippi Gulf Coast that have experienced multiple disasters. Methods: Survey administration took place in the spring of 2015 to a spatially stratified, random sample of households. This analysis included a total of 294 subjects who lived in 1 of the 3 counties of the Mississippi Gulf Coast at the time of both Hurricane Katrina in 2005 and the Deepwater Horizon oil spill in 2010. The survey included the Communities Advancing Resilience Toolkit (CART) scale, the Connor-Davidson Resilience Scale (CD-RISC 10), and the Center for Epidemiologic Studies Depression Scale (CES-D). Results: There was a significant inverse relationship between psychological resilience and depressive symptoms and a significant positive relationship between community resilience and psychological resilience. The results also revealed that community resilience was indirectly related to depressive symptoms through the mediating variable of psychological resilience. Conclusions: These findings highlight the importance of psychological resilience in long-term disaster recovery and imply that long-term recovery efforts should address factors associated with both psychological and community resilience to improve mental health outcomes. ( Disaster Med Public Health Preparedness . 2018;12:241–248)